AN ANALYSIS OF ONLINE AND TRADITIONAL EDUCATION IN STUDENT LEARNING - Kamalova Nigora,; Tajenova Gulziya, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: Online education, together with traditional education programs, has become a comprehensive learning method for both present and future generations. The main reason for this development is that online education provides wide opportunities and significant technological advantages. Through case studies and quantitative analysis, this study compares online education with traditional face-to-face education, focusing on their advantages, limitations, teaching methodologies, and student engagement. Online learning allows students to overcome the limits of time and space, while traditional learning provides direct interaction and immediate feedback. This study highlights the teaching models that most effectively influence student achievement, engagement, and learning preferences in order to foster an effective and inclusive educational future.